Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Diabetes Melitus Tipe II Diruang Interne RSUD Padang Pariaman Tahun 2026 - Haura Najwa Tsany; Hilma Yessi; Debby Silvia Dewi; Mike Asmaria (CV. ITTC INDONESIA, 2026)
Diabetes mellitus (DM) is a disease that disrupts the body's metabolism caused by insulin production not being able to work optimally. Globally, the number of sufferers will reach 589 million people in 2024 with a mortality rate of 3.4 people. Indonesia ranks 5th in the world with 20.4 million sufferers. At Padang Pariaman Regional Hospital, this disease is ranked 4th out of 10 diseases with 567 cases in 2025, and shows an increasing trend in the internal room. The purpose of this author is to implement comprehensive medical-surgical nursing care for patients with type II diabetes mellitus. The method used is a case study of Mrs. S in the internal room of Padang Pariaman Regional Hospital on February 26-March 2, 2026. The results of case study show 5 main nursing problems which include unstable blood glucose levels, acute pain, impaired skin integrity, activity intolerance, and risk of infection. Evaluation showed a GDS level of 184 mg/dl, decreased pain to a scale of 2, and improved wound condition and patient activity, all resolved within 5 days. The risk of infection resolved within 4 days. The family is expected to play an active role in supporting the patient's adherence to medication, diet, physical activity, routine checkups, and wound care to prevent further complications.